2009
DOI: 10.1115/1.4000049
|View full text |Cite
|
Sign up to set email alerts
|

Transient Methods of Thermal Properties Measurement on Fibrous Materials

Abstract: Fibrous material is a complex porous medium and steady test methods are the main test approaches we currently depend on to study the heat transfer properties. The application of unsteady test methods on fibrous material is still not mature. In this paper, some systematic studies are taken to investigate this problem. By analyzing the main factors impacting the test results, it is found that the local heat convection potentially excited by imposing test temperature can be avoided by limiting the internal temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…In this paper, the steady and the transient methods, respectively for the same material samples are used. Among several transient state methods [20,21], the flash method has been considered as it is the main technique for indirect thermal conductivity measurement of solids [22] since that method directly determine first thermal diffusivity. DSC is chosen because it performs quick measurements using small samples, takes into account the experimental time which modifies the output signal in the calorimeter (differential power ) [23] and some authors [8,24] demonstrated its feasibility with low thermal conductivity solid materials.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In this paper, the steady and the transient methods, respectively for the same material samples are used. Among several transient state methods [20,21], the flash method has been considered as it is the main technique for indirect thermal conductivity measurement of solids [22] since that method directly determine first thermal diffusivity. DSC is chosen because it performs quick measurements using small samples, takes into account the experimental time which modifies the output signal in the calorimeter (differential power ) [23] and some authors [8,24] demonstrated its feasibility with low thermal conductivity solid materials.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The details of the technique as applied to variety of systems and geometries can be found in previous studies. 2,4,7,8 Both the methods discussed above give a direct measure of thermal conductivity and can be used for anisotropic and porous materials. The methods can also provide thermal conductivity in through-thickness (axial) and in-plane (radial) directions, either by proper placement of sample in the equipment or by using special software usually supplied by the vendor.…”
Section: Overview Of the Thermal Conductivity Characterization Methods For Anisotropic Porous And Fibrous Materialsmentioning
confidence: 99%
“…Experimental thermal conductivity determination based on direct measurements of dry fibrous preforms is especially challenging due to the multiple heat transfer modes (convection, conduction, and radiation) and their complex interactions with their inherent porosity and low density. 1,2 Depending on the preform architecture, poor contact between the fibrous preforms and the measuring probes may also be a troublesome issue that has to be dealt with if contact measurement methods are used. Another challenge related to direct dry preforms measurements is that it may be impossible to differentiate the anisotropic thermal conductivities in different in-plane directions, which may be important and desired for certain applications.…”
Section: Introductionmentioning
confidence: 99%
“…The hot source which works both as heat source and temperature sensor experiences voltage variations as a single or multiple heat pulses are applied to the sample. Using the voltage feedback, the diffusivity along the given directions will be calculated [6,7]. Gustafsson [8,9] proposed a modified version of this method that is capable of accommodating the measurement of anisotropic materials.…”
Section: Introductionmentioning
confidence: 99%